Topics in ecological and environmental microbiology - Schmidt, Thomas M. (Thomas Mitchell), 1956-; Schaechter, Moselio (Amsterdam : Academic Press, 2012)
'In 2009, the third edition of the Encyclopedia of Microbiology and the Desk Encyclopedia of Microbiology published, providing customers with a six-volume compendium and condensed reference, respectively, on the vast subject of microbiology. This derivative will compile thirty-two chapters from the original MRW relating to microbial ecology (the study of how microbes interact with each other and their environments) and present them in a single thematic volume that will appeal to researchers, technicians, and students in the environmental science and microbial ecology fields. Classic and cutting-edge entries on topics including air quality, marine habitats, food webs, and microbial adhesion will be fully updated by their original authors (when possible), providing a up-to-date and affordable option to those with focused research interests'--Provided by publisher.
Abridgement of: Encyclopedia of microbiology. 3rd ed. / editor-in-chief, Moselio Schaechter.
Keywords: Environmental microbiology